Refinements on eigenvalue elasticity analysis: interpretation of parameter elasticities. (30th September 2018) - Naumov, Sergey; Oliva, Rogelio
Abstract: The purpose of this article is to report on improvements on the interpretation and insights emerging from dynamic decomposition weight analysis (DDWA). These improvements emerged from efforts to further automate and expand the eigenvalue elasticity analysis methods and resolve inconsistencies in assumptions made in published reports of DDWA usage. In addition to making available to the broad system dynamics community an improved toolset to perform eigenvalue elasticity analysis, in this paper we clarify the set of assumptions needed to obtain reliable results and develop a new framework to assess the impact of model parameters on the projections of behavior modes on stock behavior. We illustrate the use of these developments by updating a previously published model analysis. The paper concludes by summarizing our findings and their implications for the further development of structural dominance analysis. © 2018 System Dynamics Society